Study on the Effect of Different Cathodic Protection Potentials on the Growth of Mixed Bacteria and Cathodic Protection Efficiency - Zeyu Zuo; Jie Zhang; Qingle Hou; Chengjun Zhang; Ke Wang; Jizhou Duan; Xilei Chen; Baorong Hou (Chemistry)
Microbiologically influenced corrosion (MIC) is one of the key causes of material failure in marine engineering, and sulfate-reducing bacteria (SRB) and iron-oxidizing bacteria (IOB) are typical representatives of anaerobic and aerobic microorganisms, respectively. These microorganisms are widely present in marine environments and can form synergistic communities on the surface of metal materials, posing a corrosion threat to them. At the same time, the presence of mixed bacteria may have an effect on cathodic protection, so this study investigates the growth metabolism of mixed SRB and IOB under different cathodic protection potentials in an impressed current cathodic protection (ICCP) system in a marine environment containing SRB and IOB. It also examines the attachment of these microorganisms to the anode and cathode, and the impact on cathodic protection efficiency. The results indicate that in a marine environment containing IOB and SRB, the cathodic protection efficiency of the ICCP system increases with the negative shift of the protection potential. A more positive cathodic protection potential promotes the adhesion of mixed bacteria on the electrode surface and the formation of a biofilm, which reduces cathodic protection efficiency. In contrast, at a cathodic protection potential of −1.05 V (SCE), bacterial growth is inhibited, and a dense crystalline corrosion film primarily composed of Fe2O3 and Fe(OH)3 forms on the cathode surface. This film effectively protects the cathodic metal, significantly mitigating MIC.